Supported bimetallic oxide Fe3O4 / NiO@CN electrode materials, their preparation methods and applications
Patent Information
- Application Number
- CN202310674484.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-30
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-05-30
AI Technical Summary
[0020](1)本发明公开的负载型双金属氧化物Fe3O4/NiO@CN电极的结构具有出色的导电性,可加速超薄CN基底和电催化剂之间的电子传输。
Smart Images

Figure CN116791101B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of oxygen evolution electrocatalyst technology, specifically relating to a method for preparing and applying a supported bimetallic oxide Fe3O4 / NiO@CN electrode material. Background Technology
[0002] To achieve the transition from fossil fuels to clean energy, electrocatalytic water splitting has become one of the most promising pathways for future green hydrogen production. This process consists of two slow half-reactions: the hydrogen evolution reaction (HER) at the cathode (involving two electrons) and the oxygen evolution reaction (OER) at the anode (involving four electrons). To significantly improve the efficiency of electrocatalytic water splitting, both the OER and HER processes must occur at relatively fast rates. HER is a thermodynamically relatively easy reaction, catalyzed by many efficient electrocatalysts at low overpotentials. However, the OER process at the anode, being a four-electron transfer reaction, is kinetically slower and has a larger reaction barrier, often leading to higher overpotentials and severely hindering the overall efficiency of electrocatalytic water splitting. In this regard, Ir or Ru oxides are considered ideal candidates for OER catalysts, but their scarcity and high cost severely impede their large-scale application. To rationally design efficient OER electrocatalysts, it is necessary to reduce the reaction overpotential, increase the active surface area, and accelerate reaction kinetics, thereby improving energy utilization efficiency. Numerous studies have shown that non-noble transition metal-based compounds and composites, particularly iron, cobalt, and nickel-based (oxy) hydroxides, can exhibit good OER performance in alkaline media. For example, Fe3O4, due to the presence of Fe... 2+ and Fe 3+ Electron transfer between molecules gives Fe3O4 its unique electronic structure. In an alkaline environment, the Fe centers of the octahedrons in Fe3O4 significantly promote water dissociation, providing H intermediates (H*) and facilitating the adsorption of OH groups. - (OH*) Currently, Fe3O4-based catalysts have been applied to alkaline industrial water electrolysis (OER) catalytic systems. However, due to the lack of active sites for H2 / O2 generation on the Fe3O4 surface, its activity as a standalone HER / OER catalyst is poor. To improve the catalytic performance of OER catalysts under alkaline conditions, introducing another catalytic active site that promotes water splitting near its catalytic active site is one effective strategy. NiO, as a typical representative of nickel-based materials, has been extensively studied in the OER field. However, most single nickel-based catalysts exhibit high overpotentials, and the Ni formed on the NiO surface... 3+Its structure is unstable, making it unsuitable as a standalone OER electrocatalyst. In this context, introducing a bimetallic oxide heterostructure as the active interface of the electrocatalyst is a novel strategy, as the heterostructure can modulate the surface electronic structure, accelerate the charge transfer reaction kinetics, and thus improve catalytic performance.
[0003] Against this background, this invention provides an ultrathin CN-based supported bimetallic oxide Fe3O4 / NiO electrode material for electrocatalytic oxygen evolution reaction (OER). Due to its excellent conductivity, dual-active-site heterogeneous interface, and environmentally friendly and pollution-free properties, this catalyst is a promising potential OER catalytic material. This invention explores different Fe-Ni molar ratios in the bimetallic oxide to provide a preparation method and optimized conditions for the ultrathin CN-based supported bimetallic oxide Fe3O4 / NiO@CN electrode material, enabling it to exhibit superior OER performance. Summary of the Invention
[0004] To address the aforementioned research status, this invention proposes a simple method for preparing supported bimetallic oxide Fe3O4 / NiO@CN electrode materials. This invention supports Fe3O4 / NiO bimetallic oxide electrodes on ultrathin CN substrates. The structure of this ultrathin CN substrate-supported Fe3O4 / NiO bimetallic oxide electrode exhibits excellent conductivity and a heterogeneous interface with dual active sites. The supported bimetallic oxide Fe3O4 / NiO@CN electrode material was explored and optimized. 4 / The effect of different FeNi molar ratios on OER activity in NiO@CN. This invention uses a supported bimetallic oxide Fe3O4 / NiO@CN electrode material for electrocatalytic water splitting experiments. Due to the good conductivity and dual-active-site heterogeneous interface of this catalyst, it exhibits good OER performance and is a promising potential OER electrode material.
[0005] To achieve the above objectives, the present invention discloses the following technical solution.
[0006] The preparation method of the above-mentioned supported bimetallic oxide Fe3O4 / NiO@CN electrode material includes the following steps:
[0007] 1) Dissolve 10g NH4Cl, 2g dicyandiamide, 0.2mmol FeCl2, and 0.2mmol NiCl2 in 30mL of deionized water and freeze-dry.
[0008] In step 1), the freezing temperature is -50°C and the drying time is 48 hours.
[0009] 2) Place 4g of freeze-dried powder in a crucible, then place it in a tube furnace and calcine at 550℃ for 2h under an argon atmosphere. After cooling to room temperature, collect the brown powder for later use.
[0010] In step 2), the room temperature is 20-25°C, and the temperature is increased from room temperature to 550°C at a rate of 5°C / min.
[0011] 3) Weigh 300 mg of brown powder and ultrasonically disperse it in 21 mL of glucose solution for 2 hours. Then transfer it to a 100 mL stainless steel hydrothermal reactor and react it at 180 °C for 10 h. After cooling to room temperature, wash it 5 times with deionized water and ethanol respectively, and then vacuum dry it overnight.
[0012] In step 3), the glucose solution concentration is 0.3 mol / L. -1 ;
[0013] In step 3), the room temperature is 20-25°C and the drying temperature is 50°C.
[0014] 4) Transfer the dried powder back to the crucible and calcine it at 1000°C for 1 hour in a tube furnace under argon protection. After cooling to room temperature, the collected black product is the electrode material.
[0015] In step 4), the room temperature is 20-25°C, and the temperature is increased from room temperature to 1000°C at a rate of 5°C / min.
[0016] This invention further discloses the application of the supported bimetallic oxide Fe3O4 / NiO@CN electrode material in OER, which is described in detail below:
[0017] (1) In the above technical solution, the supported bimetallic oxide Fe3O4 / NiO@CN is used as an electrocatalyst.
[0018] (2) In the above technical solution, KOH aqueous solution is used as the electrolyte, and the three-electrode system for oxygen evolution is as follows: the working electrode is the ultrathin CN-substrate supported bimetallic oxide Fe3O4 / NiO@CN electrode, the counter electrode is a carbon rod, and the reference electrode is a Hg / HgO electrode. In the above technical solution, the concentration of KOH in the KOH aqueous solution is 1 mol / L. -1 .
[0019] The advantages of the supported bimetallic oxide Fe3O4 / NiO@CN electrode material and its synthesis method disclosed in this invention compared with the prior art are as follows:
[0020] (1) The structure of the supported bimetallic oxide Fe3O4 / NiO@CN electrode disclosed in this invention has excellent conductivity, which can accelerate the electron transport between the ultrathin CN substrate and the electrocatalyst.
[0021] (2) The heterogeneous interface between the active sites of bimetallic oxides is beneficial to increasing the exposure of electrocatalytic active sites, thereby improving the OER reaction activity; among them, Fe3O4, due to its unique electronic structure, can effectively promote the dissociation of water molecules and can effectively adsorb OH. - NiO species readily form Ni on their surface 3+ The structure is the true active center of the OER reaction; the introduction of Fe3O4 can stabilize Ni. 3+ The structure is optimized to further enhance OER activity. The synergistic catalytic effect of the two significantly enhances the OER electrocatalytic activity of the catalyst under alkaline conditions, while also exhibiting high electrochemical stability.
[0022] (3) The supported bimetallic oxide Fe3O4 / NiO@CN disclosed in this invention is a simple and easy-to-operate electrocatalyst for OER reaction. It is environmentally friendly and has high catalytic activity as an OER electrocatalyst. It provides a basis for the design and development of low-cost, high-activity and high-stability OER electrocatalysts in alkaline solutions. Attached Figure Description
[0023] Figure 1 The image shows the X-ray powder diffraction (XRD) pattern of the supported bimetallic oxide Fe3O4 / NiO@CN electrode material obtained in Example 1, illustrating that the Fe3O4 / NiO composite species were successfully loaded onto the CN substrate.
[0024] Figure 2 The images show scanning electron microscope (SEM) and transmission electron microscope (TEM) images of the supported bimetallic oxide Fe3O4 / NiO@CN electrode material obtained in Example 1, illustrating that the bimetallic oxide particles have uniform size, a particle size of 90 nm, and form a clear heterogeneous interface.
[0025] Figure 3 The supported bimetallic oxide Fe3O4 / NiO@CN electrode material obtained in Example 1 was used as an OER electrode in 1 mol L -1 The linear sweep voltammetry curve in KOH aqueous solution indicates that the electrode material has good OER performance.
[0026] Figure 4 The Tafel slope curves of the series of supported bimetallic oxide Fe3O4 / NiO@CN electrode materials obtained in Example 1 as OER electrodes indicate that the electrode material has fast kinetic characteristics.
[0027] Figure 5 The chronocurrent curve of the supported bimetallic oxide Fe3O4 / NiO@CN electrode material obtained in Example 1 as an OER electrode at an overpotential of 305.7 mV shows that the electrode material has good stability.
[0028] This invention further investigates the effect of different FeNi ratios in the supported bimetallic oxide Fe3O4 / NiO@CN electrode material on OER performance, using Fe3O4 / NiO molar ratios of Fe / Ni = 1:1, 1 / 3:1, 1 / 2:1, 2:1, and 3:1 as typical examples for further illustration: Detailed Implementation
[0029] The present invention will now be described through specific embodiments. Unless otherwise specified, all technical means used in the present invention are methods well known to those skilled in the art. Furthermore, the embodiments should be understood as illustrative, not limiting the scope of the invention; the essence and scope of the invention are defined only by the claims. For those skilled in the art, various changes or modifications to the material composition and dosage in these embodiments without departing from the essence and scope of the invention also fall within the protection scope of the invention. The technical solutions of the present invention will be further described below with reference to specific embodiments.
[0030] Example 1
[0031] A method for preparing a supported bimetallic oxide Fe3O4 / NiO@CN electrode material includes the following steps:
[0032] 1) Dissolve 10g NH4Cl, 2g dicyandiamide, 0.2mmol FeCl2, and 0.2mmol NiCl2 in 30mL of deionized water and freeze-dry.
[0033] 2) Place 4g of freeze-dried powder in a crucible, then place it in a tube furnace and heat it to 550°C at a heating rate of 5°C / min under an argon atmosphere. Hold the temperature for 2 hours and cool it to room temperature. Collect the brown powder for later use.
[0034] 3) Weigh 300 mg of brown powder and ultrasonically disperse it in 21 mL of 0.3 M glucose solution for 2 hours. Then transfer it to a 100 mL stainless steel hydrothermal reactor and react it at 180 °C for 10 h. After cooling to room temperature, wash it 5 times with deionized water and ethanol respectively, and then vacuum dry it overnight at 50 °C.
[0035] 4) Transfer the dried powder back to the crucible and heat it to 1000℃ in a tube furnace under argon protection at a heating rate of 5℃ / min, and hold at that temperature for 1 hour. After cooling to room temperature, the collected black product was named Fe3O4 / NiO@CN-1 (Fe / Ni = 1:1).
[0036] The XRD pattern of the Fe3O4 / NiO@CN-1 material is shown below. Figure 1 As shown, the characteristic peaks in the spectrum are consistent with the JCPDS cards of Graphite 2H (No. 75-1621), NiO (No. 87-1621), and Fe3O4 (No. 88-0315), indicating that high-purity Fe3O4 / NiO@CN-1 material has been obtained.
[0037] Scanning electron microscope (SEM) image of the supported bimetallic oxide Fe3O4 / NiO@CN electrode material (Fe3O4 / NiO@CN-1 (Fe / Ni = 1:1)) is shown below. Figure 2 As shown in Figure a, the prepared material exhibits an amorphous sheet-like structure; the transmission electron microscope image of the Fe3O4 / NiO@CN-1 material is shown in Figure a. Figure 2 As shown in b, this indicates that uniformly sized nanoparticles (approximately 90 nm) are loaded onto the ultrathin CN substrate; further... Figure 2 The nanoparticles in b are locally magnified, such as Figure 2 As shown in c, it can be clearly seen that two different sizes of lattice stripes are distributed on both sides of the interface. Through measurement, it was found that the spacing between the two lattice stripes is 0.204nm and 0.199nm, respectively, which correspond to the (111) crystal plane of NiO and the (311) crystal plane of Fe3O4 species, respectively. This indicates that the bimetallic oxides Fe3O4 and NiO were successfully loaded on the ultrathin CN substrate and formed a heterogeneous interface.
[0038] The supported bimetallic oxide Fe3O4 / NiO@CN electrode material (Fe3O4 / NiO@CN-1 (Fe / Ni=1:1)) obtained in Example 1 was used as an OER electrode for testing:
[0039] Assembly of the water electrolysis device: The electrocatalyst performance was tested using a three-electrode system. The supported bimetallic oxide Fe3O4 / NiO@CN electrode material obtained in Example 1 (Fe3O4 / NiO@CN-1 (Fe / Ni = 1:1)) was used as the working electrode, a carbon rod as the counter electrode, and an Hg / HgO electrode as the reference electrode. The electrolyte was a 1M KOH aqueous solution. The testing instruments used were a Solartron 1260 and a Solartron 1287 potentiostat system.
[0040] Electrochemical performance study:
[0041] Figure 3 The supported bimetallic oxide Fe3O4 / NiO@CN electrode material (Fe3O4 / NiO@CN-1 (Fe / Ni=1:1)) was used as an OER electrode in 1 mol L -1Linear sweep voltammetry curves in KOH aqueous solution. The figure shows that the Fe3O4 / NiO@CN-1 electrode material exhibits good electrocatalytic oxygen evolution performance, with a current density reaching 10 mA cm⁻¹. -2 At that time, the corresponding overpotential was only 305.7mV.
[0042] Figure 4 The Tafel slope curves for the supported bimetallic oxide Fe3O4 / NiO@CN electrode material (Fe3O4 / NiO@CN-1 (Fe / Ni = 1:1)) as an OER electrode are shown in the figure. The figure indicates that the Fe3O4 / NiO@CN-1 electrode material exhibits a relatively low Tafel slope (57.4 mV dec). -1 This demonstrates that it has relatively fast OER catalytic reaction kinetics.
[0043] Figure 5 The chronoamperometry curves of the supported bimetallic oxide Fe3O4 / NiO@CN electrode material (Fe3O4 / NiO@CN-1 (Fe / Ni = 1:1)) as an OER electrode are shown at an overpotential of 305.7 mV. As can be seen from the figure, during continuous electrolysis at a constant potential of 305.7 mV for 11 h, the polarization current did not show a significant decay trend, demonstrating that the Fe3O4 / NiO@CN-1 electrode material possesses excellent oxygen evolution catalytic activity and stability in alkaline electrolytes, and has potential practical application value.
[0044] Example 2
[0045] A method for preparing a supported bimetallic oxide Fe3O4 / NiO@CN electrode material, the steps of which are the same as in Example 1, except that:
[0046] 1) Dissolve 10g NH4Cl, 2g dicyandiamide, 0.07mmol FeCl2, and 0.2mmol NiCl2 in 30mL of deionized water and freeze-dry.
[0047] 2) Place 4g of freeze-dried powder in a crucible, then place it in a tube furnace and heat it to 550°C at a heating rate of 5°C / min under an argon atmosphere. Hold the temperature for 2 hours and cool it to room temperature. Collect the brown powder for later use.
[0048] 3) Weigh 300 mg of brown powder and ultrasonically disperse it in 21 mL of 0.3 M glucose solution for 2 hours. Then transfer it to a 100 mL stainless steel hydrothermal reactor and react it at 180 °C for 10 h. After cooling to room temperature, wash it 5 times with deionized water and ethanol respectively, and then vacuum dry it overnight at 50 °C.
[0049] 4) Transfer the dried powder back to the crucible and heat it to 1000℃ in a tube furnace under argon protection at a heating rate of 5℃ / min, and hold at that temperature for 1 hour. After cooling to room temperature, the collected black product is named Fe3O4 / NiO@CN-1 / 3 (Fe / Ni=1 / 3:1).
[0050] Example 3
[0051] A method for preparing a supported bimetallic oxide Fe3O4 / NiO@CN electrode material, the steps of which are the same as in Example 1, except that:
[0052] 1) Dissolve 10g NH4Cl, 2g dicyandiamide, 0.1mmol FeCl2, and 0.2mmol NiCl2 in 30mL of deionized water and freeze-dry.
[0053] 2) Place 4g of freeze-dried powder in a crucible, then place it in a tube furnace and heat it to 550°C at a heating rate of 5°C / min under an argon atmosphere. Hold the temperature for 2 hours and cool it to room temperature. Collect the brown powder for later use.
[0054] 3) Weigh 300 mg of brown powder and ultrasonically disperse it in 21 mL of 0.3 M glucose solution for 2 hours. Then transfer it to a 100 mL stainless steel hydrothermal reactor and react it at 180 °C for 10 h. After cooling to room temperature, wash it 5 times with deionized water and ethanol respectively, and then vacuum dry it overnight at 50 °C.
[0055] 4) Transfer the dried powder back to the crucible and heat it to 1000℃ in a tube furnace under argon protection at a heating rate of 5℃ / min, and hold at that temperature for 1 hour. After cooling to room temperature, the collected black product is named Fe3O4 / NiO@CN-1 / 2 (Fe / Ni=1 / 2:1).
[0056] Example 4
[0057] A method for preparing a supported bimetallic oxide Fe3O4 / NiO@CN electrode material, the steps of which are the same as in Example 1, except that:
[0058] 1) Dissolve 10g NH4Cl, 2g dicyandiamide, 0.4mmol FeCl2, and 0.2mmol NiCl2 in 30mL of deionized water and freeze-dry.
[0059] 2) Place 4g of freeze-dried powder in a crucible, then place it in a tube furnace and heat it to 550°C at a heating rate of 5°C / min under an argon atmosphere. Hold the temperature for 2 hours and cool it to room temperature. Collect the brown powder for later use.
[0060] 3) Weigh 300 mg of brown powder and ultrasonically disperse it in 21 mL of 0.3 M glucose solution for 2 hours. Then transfer it to a 100 mL stainless steel hydrothermal reactor and react it at 180 °C for 10 h. After cooling to room temperature, wash it 5 times with deionized water and ethanol respectively, and then vacuum dry it overnight at 50 °C.
[0061] 4) Transfer the dried powder back to the crucible and heat it to 1000℃ in a tube furnace under argon protection at a heating rate of 5℃ / min, and hold at that temperature for 1 hour. After cooling to room temperature, the collected black product was named Fe3O4 / NiO@CN-2 (Fe / Ni = 2:1).
[0062] Example 5
[0063] A method for preparing a supported bimetallic oxide Fe3O4 / NiO@CN electrode material, the steps of which are the same as in Example 1, except that:
[0064] 1) Dissolve 10g NH4Cl, 2g dicyandiamide, 0.6mmol FeCl2, and 0.2mmol NiCl2 in 30mL of deionized water and freeze-dry.
[0065] 2) Place 4g of freeze-dried powder in a crucible, then place it in a tube furnace and heat it to 550°C at a heating rate of 5°C / min under an argon atmosphere. Hold the temperature for 2 hours and cool it to room temperature. Collect the brown powder for later use.
[0066] 3) Weigh 300 mg of brown powder and ultrasonically disperse it in 21 mL of 0.3 M glucose solution for 2 hours. Then transfer it to a 100 mL stainless steel hydrothermal reactor and react it at 180 °C for 10 h. After cooling to room temperature, wash it 5 times with deionized water and ethanol respectively, and then vacuum dry it overnight at 50 °C.
[0067] 4) Transfer the dried powder back to the crucible and heat it to 1000℃ in a tube furnace under argon protection at a heating rate of 5℃ / min, and hold at that temperature for 1 hour. After cooling to room temperature, the collected black product was named Fe3O4 / NiO@CN-3 (Fe / Ni = 3:1).
[0068] This invention further illustrates the invention using supported pure metal oxides Fe3O4@CN and NiO@CN as typical examples:
[0069] Example 6
[0070] A method for preparing a supported pure metal oxide Fe3O4@CN electrode material, the steps of which are the same as in Example 1, except that:
[0071] 1) Dissolve 10g NH4Cl, 2g dicyandiamide, and 0.2mmol FeCl2 in 30mL of deionized water and freeze-dry.
[0072] 2) Place 4g of freeze-dried powder in a crucible, then place it in a tube furnace and heat it to 550°C at a heating rate of 5°C / min under an argon atmosphere. Hold the temperature for 2 hours and cool it to room temperature. Collect the brown powder for later use.
[0073] 3) Weigh 300 mg of brown powder and ultrasonically disperse it in 21 mL of 0.3 M glucose solution for 2 hours. Then transfer it to a 100 mL stainless steel hydrothermal reactor and react it at 180 °C for 10 h. After cooling to room temperature, wash it 5 times with deionized water and ethanol respectively, and then vacuum dry it overnight at 50 °C.
[0074] 4) Transfer the dried powder back to the crucible and heat it to 1000℃ in a tube furnace under argon protection at a heating rate of 5℃ / min, and hold at that temperature for 1 hour. After cooling to room temperature, the collected black product was named Fe3O4@CN.
[0075] Example 7
[0076] A method for preparing a supported pure metal oxide NiO@CN electrode material, the steps of which are the same as in Example 1, except that:
[0077] 1) Dissolve 10g NH4Cl, 2g dicyandiamide, and 0.2mmol NiCl2 in 30mL of deionized water and freeze-dry.
[0078] 2) Place 4g of freeze-dried powder in a crucible, then place it in a tube furnace and heat it to 550°C at a heating rate of 5°C / min under an argon atmosphere. Hold the temperature for 2 hours and cool it to room temperature. Collect the brown powder for later use.
[0079] 3) Weigh 300 mg of brown powder and ultrasonically disperse it in 21 mL of 0.3 M glucose solution for 2 hours. Then transfer it to a 100 mL stainless steel hydrothermal reactor and react it at 180 °C for 10 h. After cooling to room temperature, wash it 5 times with deionized water and ethanol respectively, and then vacuum dry it overnight at 50 °C.
[0080] 4) Transfer the dried powder back to the crucible and heat it to 1000℃ in a tube furnace under argon protection at a heating rate of 5℃ / min, and hold at that temperature for 1 hour. After cooling to room temperature, the collected black product is named NiO@CN.
[0081] Example 8
[0082] RuO2 is a commonly used commercial OER electrode material. Commercially available RuO2 (99.95% purity) was used as the working electrode for OER catalytic activity testing.
[0083] This invention discloses the application prospects of supported bimetallic oxide Fe3O4 / NiO electrode materials in the field of electrocatalytic oxygen evolution:
[0084] The electrodes obtained in Examples 1-8 were used for testing:
[0085] Assembly of the water electrolysis device: The electrocatalyst performance was tested using a three-electrode system, in which the electrode materials obtained in Examples 1-8 were used as the working electrode, the carbon rod as the counter electrode, and the Hg / HgO electrode as the reference electrode. The electrolyte was a 1M KOH aqueous solution. The testing instruments used were a Solartron 1260 and a Solartron 1287 potentiostat system.
[0086] Electrochemical performance studies were conducted on the prepared electrode materials:
[0087] Test at 1 mol L -1 Linear sweep voltammetry curves were obtained from KOH aqueous solution to obtain the current density when it reaches 10 mA / cm². -2 At that time, the corresponding overpotential and Tafel slope.
[0088] Appendix Table 1 compares the electrochemical test results of the supported bimetallic oxide Fe3O4 / NiO@CN electrode materials obtained under different Fe3O4 / NiO ratios: Fe / Ni = 1:1 (Example 1), Fe / Ni = 1 / 3:1 (Example 2), Fe / Ni = 1 / 2:1 (Example 3), Fe / Ni = 2:1 (Example 4), and Fe / Ni = 3:1 (Example 5) in terms of electrocatalytic oxygen evolution.
[0089] Appendix 1
[0090]
[0091] As shown in Appendix Table 1, the catalyst obtained when Fe / Ni = 1:1 (Example 1) exhibits the optimal OER electrocatalytic activity, with an overpotential of only 305.7 mV and a Tafel slope of 57.4 mV. -1 .
[0092] Appendix Table 2 compares the electrochemical test results of the optimal ratio of supported metal oxide Fe3O4 / NiO@CN electrode material Fe / Ni = 1:1 (Example 1) with those of pure supported metal oxide Fe3O4 (Example 6) and pure NiO (Example 7) in terms of electrocatalytic oxygen evolution:
[0093] Appendix 2
[0094]
[0095] As shown in Appendix Table 2, the OER electrocatalytic activity of the supported bimetallic oxide Fe3O4 / NiO@CN (Example 1) is far superior to that of the pure supported pure metal oxide Fe3O4 (Example 6) and pure NiO (Example 7).
[0096] Appendix Table 3 compares the electrochemical test results of the optimal ratio of supported metal oxide Fe3O4 / NiO@CN electrode material Fe / Ni = 1:1 (Example 1) with the commercial catalyst RuO2 (Example 8) in terms of electrocatalytic oxygen evolution:
[0097] Appendix 3
[0098]
[0099] As shown in Appendix Table 3, the OER electrocatalytic activity of the supported bimetallic oxide Fe3O4 / NiO@CN (Example 1) is far superior to that of the commercial RuO2 catalyst, and it has broad application prospects.
Claims
1. A method for preparing a supported bimetallic oxide Fe3O4 / NiO@CN electrode material, characterized in that... Follow these steps: 1) Dissolve 10g NH4Cl, 2g dicyandiamide, 0.2mmol FeCl2, and 0.2mmol NiCl2 in 30mL of deionized water and freeze-dry. 2) Place 4g of freeze-dried powder in a crucible, then place it in a tube furnace and calcine at 550℃ for 2h under an argon atmosphere. After cooling to room temperature, collect the brown powder for later use. 3) Weigh 300 mg of brown powder and ultrasonically disperse it in 21 mL of glucose solution for 2 hours. Then transfer it to a 100 mL stainless steel hydrothermal reactor and react at 180 °C for 10 hours. After cooling to room temperature, wash it five times with deionized water and ethanol, and then vacuum dry it overnight. The glucose solution concentration is 0.3 mol / L. -1 ; 4) Transfer the dried powder back to the crucible and calcine it in a tube furnace at 1000°C for 1 hour under argon protection. After cooling to room temperature, the collected black product is the electrode material. The room temperature mentioned in steps 2), 3), and 4) above is 20-25°C.
2. According to the preparation method of claim 1, in step 1), the freezing temperature is -50°C and the drying time is 48h.
3. According to the preparation method of claim 1, in step 2), the temperature is raised to 550°C at a rate of 5°C / min.
4. According to the preparation method of claim 1, in step 3), the vacuum drying temperature is 50°C.
5. According to the preparation method of claim 1, in step 4), the temperature is raised to 1000°C at a rate of 5°C / min.
6. The application of the supported bimetallic oxide Fe3O4 / NiO@CN electrode material as described in claim 1 in the oxygen evolution reaction.
7. In the application according to claim 6, KOH aqueous solution is used as electrolyte, and the three-electrode system of the reaction is: working electrode is Fe3O4 / NiO@CN electrode, counter electrode is carbon rod, and reference electrode is Hg / HgO electrode.
8. The application according to claim 7, wherein the concentration of KOH in the KOH aqueous solution is 1 mol / L. -1 .